Validação de método multirresíduos para análise de praguicidas em músculo bovino por LC- MS/MS - Jennifer Mattedi Gobbi (2016)
The improper use of pesticides can cause various losses that directly affect the environment and animals. It can also indirectly, affect products such as meat, due to its bioaccumulation characteristics, environmental persistence and toxicity. This paper presents the data obtained in the validation study of a development multi-residues method to detect 188 pesticides in bovine muscle, different classes of insecticides, fungicides, herbicides, miticides and nematicides. Using bovine muscle, this study aimed to verify the efficiency and applicability of the QuEChERS method modified with the extraction of pesticide residues, development and validation detection methods and quantification of pesticide residues by LC-MS / MS and verify the presence of pesticides in commercial samples. The choice for extraction technique was the QuEChERS with modification and the equipment used for analysis, was the LC-MS / MS system. The validation of the method multi-residues met the performance criteria proposed by the Ministry of Agriculture of the Validation Guide, Livestock and Supply. After the appropriate tests and adjustments to validate the multi-residue method, tests were performed for 188 pesticides in 108 samples coming from the PNCRC, 171 met the acceptance criteria, with recovery 70-120% CV less than or equal to 20% and expanded uncertainty of less than 50 %. The quantization limit of the method was 0.01 and 0.025 mg.kg-1 and the detection limit was 0,005 mg.kg-1. Intermediate precision of the method was evaluated by the results obtained and the tests conducted with recovery levels 0.01; 0.025; 0.05 and 0.10 mg.kg-1. We analyzed 32 samples of commercial beef from the northwestern region of Belo Horizonte and have not found the pesticides validated by the method.